Leadership Characteristics with Potential for Added Value Management by Integrating Relevant Features from Modernized Leadership of Vocational School Administrators - Thunkarn Akaradechdecha; Malai Tawisook; Chira Honglaradom (My University, 2019)
Abstract As current social and technological developments cause increasingly rapid change, it is more important than ever that institutional administrators implement leadership practices that add value to their organizations and ensure competitiveness in the digital era. For the vocational colleges which shape students to contribute to society’s economy as part of its workforce, the study of leadership characteristics can potentially create added value through management by integrating the V4 concept, called Happiness Value, into the leadership of executives. The research aimed to determine and examine these characteristics for modernized leadership of private education institutions using the Delphi method and the results of the study show that leaders have the ability to maximize value, in addition to institutional integrity and sustainability, through management integrating the Happiness Value concept, with five important leadership features being: 1) potential for ideas and creativity, 2) work processes, 3) interpersonal relationships, 4) communication and 5) information systems technology.
Keywords: Value (mathematics); Delphi Method; Leadership, Behavior, and Decision-Making Studies